2022
DOI: 10.3389/fpsyt.2021.812667
|View full text |Cite
|
Sign up to set email alerts
|

A Feasibility Study of the WHO Digital Mental Health Intervention Step-by-Step to Address Depression Among Chinese Young Adults

Abstract: Background: Chinese young adults experience barriers to mental health treatment, including the lack of treatment providers and stigma around treatment seeking. Evidence-based digital mental health interventions are promising and scalable alternatives to face-to-face treatment for this population, but lack rigorous evidence to support scale-up in China.Aim: The study was a feasibility study for a large-scale RCT of Step-by-Step, a behavioral activation-based, mental health intervention to address depression and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(46 citation statements)
references
References 50 publications
(64 reference statements)
1
26
0
Order By: Relevance
“…The interventions proposed in the included studies can be divided into two broad categories: social support and coping strategies. Social support was provided by government authorities [ 49 , 52 - 54 , 61 , 62 , 68 , 72 , 84 , 86 - 88 ]; university authorities [ 12 , 48 , 50 , 51 , 53 - 55 , 57 - 59 , 62 , 64 , 65 , 67 , 69 , 91 , 93 ]; students’ affairs counselors and teachers [ 54 , 75 , 83 - 85 , 87 , 93 ]; family members [ 52 , 54 , 57 , 83 , 94 ]; health care authorities and professionals [ 52 , 63 , 66 , 75 , 77 - 79 , 87 ]; researchers [ 70 , 85 ]; and media-, internet-, and smartphone-based interventions [ 26 , 53 , 55 , 56 , 60 , 71 , 73 , 75 , 77 , 80 , 81 ]. Positive coping strategies were adopted by undergraduate students themselves [ 52 , 82 , 83 , 85 , 86 ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The interventions proposed in the included studies can be divided into two broad categories: social support and coping strategies. Social support was provided by government authorities [ 49 , 52 - 54 , 61 , 62 , 68 , 72 , 84 , 86 - 88 ]; university authorities [ 12 , 48 , 50 , 51 , 53 - 55 , 57 - 59 , 62 , 64 , 65 , 67 , 69 , 91 , 93 ]; students’ affairs counselors and teachers [ 54 , 75 , 83 - 85 , 87 , 93 ]; family members [ 52 , 54 , 57 , 83 , 94 ]; health care authorities and professionals [ 52 , 63 , 66 , 75 , 77 - 79 , 87 ]; researchers [ 70 , 85 ]; and media-, internet-, and smartphone-based interventions [ 26 , 53 , 55 , 56 , 60 , 71 , 73 , 75 , 77 , 80 , 81 ]. Positive coping strategies were adopted by undergraduate students themselves [ 52 , 82 , 83 , 85 , 86 ,…”
Section: Resultsmentioning
confidence: 99%
“…Evidence-based digital mental health interventions were found to be useful in improving mental health concerns [ 56 , 60 ], because depressed undergraduate students became less hostile when logging onto the internet, suggesting the internet as a useful medium to provide treatment for people with depression [ 71 ]. In the context of face-to-face intervention delivery hindered by the COVID-19 pandemic, internet-delivered interventions such as internet-delivered cognitive behavioral therapy can be considered to address effects of social networking service addiction on the mental health status of Chinese university students [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Step-by-Step was developed by the World Health Organization, the Ministry of Health in Lebanon, the University of Zurich, and Freie Universität Berlin ( Burchert et al, 2019 ; Carswell et al, 2018 ). The Chinese version of Step-by-Step was culturally adapted and pilot tested in Macao with support from the WHO ( Sit et al, 2020 , Sit et al, 2022 ). The intervention is brief (5-sessions), delivered via mobile app, designed to address depression, but is also expected to be transdiagnostic (i.e., also addresses anxiety, PTSD, other stress reactions and client-defined psychosocial problems), and covers general wellbeing.…”
Section: Methodsmentioning
confidence: 99%
“…The core therapeutic component of Step-by-Step is behavioral activation ( Carswell et al, 2018 ; Dawson et al, 2015 ). It has undergone technical adaptation for Syrian refugees in Germany, Sweden, and Egypt ( Burchert et al, 2019 ), culturally adapted for Overseas Filipino workers (OFWs) ( Garabiles et al, 2019 ), Syrian refugees, Lebanese, and Palestinians in Lebanon ( Abi Ramia et al, 2018 ), and Chinese young adults ( Sit et al, 2020 ) and showed promising preliminary results in these populations ( Harper Shehadeh et al, 2019 ; Heim et al, 2021 ; Sit et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%